Konstytucjonalizm jako refleksja - Pichlak, Maciej (Filozofia Publiczna i Edukacja Demokratyczna, 2018)
The objective of the paper is to present various forms of constitutionalism, with a special focus on constitutionalism understood as a form of reflection of political community. The paper adopts the perspective of reflexivity theory in order to reconstruct the basic alternatives in that regard, and also to reveal their potential advant ges and weaknesses. As it is demonstrated, it is precisely philosophical and sociological conceptions of reflexivity that are particularly suitable for understanding the specificities of constitutionalism – indeed, the latter, as a discourse about the foundations of the political and legal existence of a given community, inevitably assumes the form of reflection. The special focus within the paper is devoted to two key distinctions within the sphere of reflexivity theory, which impact the manner in which constitutional reflection is performed. The first of the distinctions concerns the relationship of reflection to tradition, while the second is done according to the criterion of the logical structure of reflexive cognizance. It is argued here that the dominant version of modern constitutionalism prescribes that constitutional reflexion be perceived as a closed process with the objective of emancipation from tradition. An alternative to this mainstream approach can be proposed in the form of capturing constitutionalism as reflexion with its foundation in tradition, at the same time dialogically mediated in other forms of social and political discourse.